A Research of Corporate Social Disclosures in the U.K. and China: Banking Firms - Yang, Sen (2010)
This study aims to offer an empirical analysis of practices and characteristics of the banking firms in both the UK and China on the basis of the corporate social and environmental disclosure in the firms’ annual reports. The results show that there are three key factors which can significantly affect the disclosure of corporate social responsibility in the banking industry, the country, firm size, and industry types. The analysis reports that the level of the adoption and practices of corporate social and environmental disclosures in China is far behind the UK. In the UK, there is a significant positive relationship between the firm size and the total CSR disclosure, while this relationship cannot be supported in the analysis of Chinese banks. Comparing the UK banking industry and utility industry, the result states that the firms in these two industries are different in both quantity and the intensive themes of the CSR disclosures.